Global research hotspots and trends of theta burst stimulation from 2004 to 2023: a bibliometric analysis - Liu, Mingyue; Jin, Shasha; Liu, Mengya; Yang, Bin; Wang, Qian; Fan, Chunliang; Li, Zhe; Wu, Liang (Frontiers in Neurology, 2024)
BackgroundTheta burst stimulation (TBS) has garnered widespread attention in the scientific community, but a comprehensive bibliometric analysis of TBS research remains absent. This study aims to fill this gap by elucidating the characteristics, hotspots, and trends in TBS publications over the past 20 years using bibliometric methods.MethodsWe retrieved TBS-related publications from January 1, 2004, to December 31, 2023, from the Web of Science Core Collection (WoSCC). The analysis focused on articles and review articles. Data were processed using the bibliometric package in R software, and CiteSpace and VOSviewer were employed for bibliometric and knowledge mapping analyses.ResultsA total of 1,206 publications were identified, with 858 included in the analysis. The annual publication volume showed a fluctuating upward trend. Leading institutions and authors were predominantly from the United States of America (USA) and European countries. Core journals and publications also primarily originated from these regions. Current research hotspots include the clinical applications and mechanisms of TBS in neurorehabilitation and depression. TBS cerebellar stimulation has emerged as a promising therapeutic target. Future research is likely to focus on dysphagia, cognitive impairments, and post-traumatic stress disorder.ConclusionThis bibliometric analysis provides an overview of the basic knowledge structure, research hotspots, and development trends in TBS research over the past two decades. The findings offer valuable insights into the evolving landscape of TBS research and its potential directions.